Underwater Noise Monitoring of a Wave Energy Converter: Insights from the HiWave-5 Project in Aguçadoura, Portugal (Proceedings of the European Wave and Tidal Energy Conference, 2025)
As Marine Renewable Energy (MRE), particularly wave energy, develops it is critical to understand and assess potential environmental interactions. Wave Energy Converters (WECs) and associated infrastructure are a source of underwater noise thus with potential to introduce acoustic disturbances that could affect marine species reliant on sound for communication, navigation, and foraging. This study presents the results of underwater noise monitoring conducted for the HiWave-5 wave energy project off the coast of Aguçadoura, Portugal. Ongoing monitoring began in 2022, during pre-operation, continuing through to 2023, covering its early operation phases. Underwater noise was evaluated across three sampling locations, through hydrophones, capturing seasonal variations during autumn/winter and spring/summer, located at increasing distances. Broadband Sound Pressure Level (SPL) and 1/3-octave bands were analysed, with a sampling frequency range of 10 Hz-288 kHz. The influence of season, wave height, wave period, temperature and WEC operation regime on acoustic emissions was analysed. During the commissioning phase, the WEC was tested in various operational states, including "Tuned" and "Derated" modes. Higher noise levels were observed under increased wave heights (> 2 m), and significantly affected by wave period and temperature. Notably, the "Tuned" mode demonstrated reduced noise emissions at lower frequencies, highlighting potential pathways for reduced impacts with technological optimisation. Future monitoring phases will further characterise long-term acoustic impacts and refine mitigation strategies.This work was part of the SafeWAVE Project co-funded by the European Climate, Infrastructure and Environment Executive Agency (CINEA), Call for Proposals EMFF-2019-1.2.1.1 - Environmental monitoring of ocean energy devices.